Digestibilidade aparente da proteína de alimentos alternativos para o acará-disco (Symphysodon discus Heckel, 1840) - Cartaxo, Jefferson Wayne da Silva (2015)
The objective of this work was to determine the apparent digestibility coefficients of crude protein from alternative ingredients (chrysalis meal of silkworm, shrimp waste meal, isolated soy protein, wheat gluten) to discus (Symphysodon discus Heckel, 1840). Diets with the tested ingredients were composed of 69.5% of the reference diet, 0.5% chromium oxide and 30% of the test ingredient. 25 fish were used (106 ± 26.6 g), over five digestibility tanks with conical bottom and 100 L of capacity. The experimental design was Latin square 5 x 5 (five diets and five periods). The determination of 37 apparent digestibility coefficient was carried out by the indirect method, using 0.5% chromic oxide (Cr2O3), as an indicator. Apparent digestibility coefficients of crude protein and digestible protein were 92.86 and 22.87% for the chrysalis meal of silkworm, 62.44 and 24.46% for the , shrimp waste meal, 93.34 and 84.44% for the isolated soy protein, 86.94 and 72.58% for wheat gluten, and 92.12 and 40.63% for the basal diet, respectively. It concludes from this that the discus uses the isolated soy protein, the chrysalis and wheat gluten in your diet efficiently, which enables its use in feed for this species.